A prospective study on parathyroid hormone levels in detecting early hypocalcemia after total thyroidectomy - A. P. V., Sunil Kumar; G., Vinay (International Surgery Journal, 2017)
Background: Hypoparathyroidism and the resultant hypocalcaemia is a major cause of postoperative morbidity after total thyroidectomy with the incidence varying from 1% to 71%. This study aims to determine the incidence of parathyroid hormone deficiency as an earliest indicator for detecting hypocalcemia following total thyroidectomy. Methods: A prospective study was carried out among 50 subjects attending Department of Surgery, K. R. Hospital, Mysuru over a period of 12 months. Subjects of either sex undergoing total thyroidectomy had their serum parathyroid hormone levels tested at 1, 4, 12 and 24 hours after surgery were included in the study. Patients with poor compliance, calcium supplementation prior to surgery, coexisting parathyroid or renal pathology were excluded from the study. Descriptive statistics and Pearson correlation coefficients were used to analyse the results. Results: Among 50 study subjects, Hypocalcemia developed in 3 subjects (6%) 24 hours after thyroidectomy showing a sensitivity, specificity, negative and positive predictive value of 91%, 100%, 98% and 96% respectively. Conclusions: Parathyroid hormone levels in postoperative total thyroidectomy is an earliest indicator to detect symptomatic hypocalcemia subjects 24 hours after surgery, which prompts early administration of oral calcium replacement therapy in high risk subjects and potential safe early discharge post-operatively.